Preventing Alzheimer's disease : personal responsibility - Barak, Yoram (Professor of Psychiatry) (Neurodegenerative diseases--laboratory and clinical research., 2013)
The prevention of dementia, and particularly of Alzheimer's disease, is a major challenge for researchers and clinicians. In this book, the mixture of evidence, observations and hypotheses in the current literature is categorized into avenues for possible preventive interventions, as suggested by the NIH State-of-the-Science Conference. The main categories are: antihypertensive medications; nutrition; cognitive engagement; volunteering and physical activity. There is, as yet, no conclusive evidence, but each category may hold promise for the prevention of dementia. The robust findings are as f.